Optimizing Big Data Driven Strategic Management to Enhance the Quality of Adaptive Contemporary Islamic Education - Prasasti Karunia Farista Ananto; Cecep Hilman; Eka Muzalfitri Ridwan; Nor Anisa (Institut Bahri Asyiq Galis Bangkalan, 2026)
Digital transformation in education has driven the utilization of large-scale data as a basis for strategic decision-making. However, Islamic education has continued to face limitations in integrating data-based approaches into its management systems, resulting in limited adaptability to change. This study aimed to analyze the optimization of big data -based strategic management in improving the quality of adaptive contemporary Islamic education. The study employed a descriptive qualitative approach with a meta-analysis method of scientific literature published between 2018 and 2025 from reputable digital databases. Data were collected through digital documentation using Boolean keyword techniques and were selected through a systematic protocol. Data analysis was conducted using content and thematic analysis to identify patterns, concepts, and relationships among variables. The findings indicated that the utilization of big data significantly enhanced the effectiveness of strategic management through the strengthening of data-driven planning, implementation, and evaluation. In addition, such integration improved the quality of Islamic education in terms of curriculum, governance, and institutional adaptability. This study contributed to the development of an integrative model of data-based Islamic education management relevant to the demands of the digital era.